The Effect of Using the Chatbot to Improve Digital Literacy Skill of Thai Elderly - Sriwisathiyakun, Kanyarat (My University, 2024)
This research aims to demonstrate the learning success and contentment of elderly people in Thailand using a chatbot innovation for improving digital literacy. Three parts of the research were carried out: Phase 1 of the research focused on developing the chatbot and any relevant educational digital media; Phase 2 engaged in pre-experimental by experts’ validation; and Phase 3 involved an experiment where the chatbot was deployed with elderly people. Samples were collected from 33 elderly people. The information was gathered through expert interviews, pretests, and posttests on chatbot usage, and satisfaction surveys. The data was then analyzed using the dependent t-test, percentage, mean, standard deviation, and content analysis. Results showed that our Senior See Net chatbot was simple to use and navigate, with an appropriate artistic appearance. Findings demonstrate that this chatbot was simple to use and access, had an appropriate creative composition, and was made up of sufficiently thorough media and content on digital literacy. Furthermore, the statistical analysis revealed that after using the chatbot, the elderly’s understanding of digital literacy improved statistically significant at the 0.05 level. Furthermore, their overall satisfaction was rated high.
Keywords: Chatbot; Digital literacy; Elderly; Learning outcome; User satisfaction